The development of a new catalytic converter and its emissions characterisics of low RPM engine - 175400 Ahmad Jais Alimin (Skudai : Universiti Teknologi Malaysia, 2001)
Thesis (Master of Engineering (Mechanical Engineering)) - Universiti Teknologi Malaysia, 2001